Catastrophes as Crime Scenes: Analysing the Legal Context - V. N. Izzo (Law Text Culture, 2009)
Catastrophes are a powerful breakdown of our normative world, due to how they affect legal systems as jurisgenerative forces and the negation of law they produce at the same time. In this article I discuss the theoretical impact that the concept of catastrophe has on legal systems. To do so I focus on the strategies of response to the consequences of catastrophes enforced by the legal systems, exploring tensions between regulatory approaches and the guarantee of fundamental rights. In the second part of the article I assess the theoretical framework developed by connecting crime scenes to the idea of catastrophe. The analysis is conducted with reference to different cases such as the Bhopal disaster, the tsunami in the Indian Ocean, hurricane Katrina and a particular case of man-made and criminal catastrophe, the extensive toxic waste devastation caused by criminal organisations in the area of Naples, in Southern Italy. These cases show the links between environmental disasters, the inefficiency of law and the massive devastation of an entire area, which leads to different kinds of crime scenes from those normally evaluated, for their source, their physical extensions and for the enormous impact they had on local communities.